Transparansi dan Integritas dalam Pemilihan Umum: Upaya Mencegah Kecurangan dan Manipulasi - Juwita Juwita; Muhammad Soultan Joefrian; Andri Rusta; Irawati; Mhd Fajri (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
Transparency and integrity are two important principles that must be upheld in the implementation of general elections. Cases of fraud that occurred in the 2019 elections such as the practice of money politics in the form of distributing money and goods (cooking oil, rice, sugar, headscarves), distributing umroh coupons such as the case that ensnared Mandala Shoji (DPR-RI candidate from PAN) and Lucky Andriani (DKI DPRD candidate from PAN). The case of voting more than once was carried out by Ridwan Benseh as an KPPS member at TPS 08 Paru Village, Bandar Baru District, Pidie Jaya Regency. Transparency and integrity is one way to prevent fraud and manipulation from occurring in general elections. The research method in this article is to use qualitative methods, qualitative methods are defined as social science research methods that collect and analyze data in the form of words. Efforts made to prevent fraud and manipulation in general elections improve the quality of election management institutions, participatory supervision of the community, the use of information technology to increase transparency.